Strategies for Handling Human Rights Violations in the Face of Political Developments in Papua - Ibrahim, Maulana Malik; Samputra, Palupi Lindiasari; Fatwa, Nur (Jurnal Locus Penelitian dan Pengabdian, 2025)
This research aims to identify the types of human rights violations that have occurred in the Papua region and to analyze the government’s strategies for addressing each violation. The increase in conflicts related to human rights violations in Papua, particularly by separatist groups, has been marked by acts of discrimination against human rights activists and security task forces. These dynamics have further impeded national economic growth and infrastructure development. The purpose of this research is to understand the nature of human rights violations in the Papua region and to examine the government’s response to these violations amid evolving political developments in Papua. This study employs a descriptive qualitative approach, analyzing 24 previous scientific articles published in reputable national and international journals from 2018 to 2025. Data were collected through searches on Google Scholar using the keyword Human Rights. The research concludes that addressing human rights issues in Papua requires deliberative dialogue conducted by the central government with all parties involved in the conflict, like the approach taken by the Indonesian government in resolving the GAM conflict.